ANALISIS PENGUKURAN KINERJA REKSA DANA SAHAM YANG TERCATAT PADA BURSA EFEK INDONESIA PADA KONDISI PASAR BULLISH DAN BEARISH - Corry Sutrisna; Yulia Efni; Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the measurement of the performance of the Equity Mutual Fund Listed in Indonesian Stock Exchange in Bullish and Bearish Market Conditions. The population in this study is a mutual fund shares listed in Indonesian Stock Exchange on July 21, 2014 until December 29, 2015 as many as 182 equity mutual fund shares. The sampling is done by using the method of pusposive sampling thus obtained a sample of 56 equity mutual fund shares. Analysis of the data used is quantitative descriptive with wilcoxon signed range test which were processed with SPSS version 17:00. The test results show that there is no significant difference between Sharpe Index equity mutual funds, Treynor Index equity mutual funds and Jensen Index equity mutual fund shares than the market performance in a bullish market conditions. There are significant differences between Sharpe Index equity mutual fund shares than the market performance on the bearish market conditions. There are no significant differences between Treynor Index equity mutual funds and Jensen Index equity mutual funds compared to market performance in the bearish market conditions. There are significant differences between Sharpe Index and Treynor Index in bullish and bearish market conditions. And there are no significant differences between Jensen Index in bullish and bearish market conditions. Investors and prospective investors should look at the performance of the equity mutual fund before investing to determine the level of benefits and risks that can be obtained and see the market conditions at the time of investingKeyword : Mutual Fund, Sharpe Index, Treynor Index, Jensen Index and Market Performance